Psychological and social factors responsible for school violence - Abdelouaheb, Soufi (Journal of Educational and Psychological Sciences, 2021)
The school violence is one of the most important topics that has attracted the interest of many researchers and specialists in psychology, education and sociology because of its complex nature for the student, teacher and the school as a whole for decades. This study was an attempt to identify the most important psychological and social factors behind the spread of violence in schools, And its interpretation through a set of theoretical theories of psychoanalysis, social learning, theory of frustration and aggression, biological theory, and the most prominent aspects of violent personality.
Keywords: psychological factors; social factors; violence; school violence